Effect of Adjusting for Baseline Stroke Severity in the National Inpatient Sample. Issue 11 (30th August 2021) - de Havenon, Adam; Sheth, Kevin N.; Johnston, Karen C.; Anadani, Mohammad; Yaghi, Shadi; Tirschwell, David; Ney, John
Abstract : Supplemental Digital Content is available in the text.